Case Report: Intraoperative detection of a rare superior vena cava variant in chest wall intravenous port implantation - Yang, Shaofeng; Du, Jing; Li, Donghai (Frontiers in Surgery, 2025)
As a fully implantable central venous infusion device, venous access port (VAP) is widely used in long-term tumor chemotherapy and parenteral nutrition due to its long maintenance cycle and high patient comfort, and is usually divided into upper arm port and chest wall port. Chest wall port is usually implanted by internal jugular vein or subclavian vein access, and the device is placed in a pocket in the chest wall subcutaneously, which is a widely used totally implantable venous access port (TIVAP) in recent years, and has the advantages of long retention time and low complication rate compared with peripherally inserted central venous catheter (PICC). Here, we report a case of incidental diagnosis of persistent left superior vena cava (PLSVC) during the implantation of chest wall IV port after rectal cancer surgery. In patients undergoing IV port implantation, congenital venous variations were found to commonly result in ectopic catheter ends. Postoperative catheter malfunction, thrombosis, and cardiac arrhythmias have all been associated with catheter tip location, and accordingly, we conducted a comprehensive review of this case with the aim of improving the safety of infusion port implantation inpatients.